Analisis Persepsi Masyarakat Terhadap Bank Syariah (Studi Kasus di Kelurahan Air Tiris Kecamatan Kampar) - Ibrahim, Zafran (International Journal Labs, 2025)
Air Tiris Village is located in Kampar District, with a predominantly Muslim population. However, most Muslims in this village still have minimal understanding of Islamic banking. Islamic banks are financial institutions that collect funds from the public and distribute them to the community through commercial operational systems and mechanisms based on Islamic law as stipulated in the Quran and Hadith. This study aims to obtain information about the views of the community in the village regarding Islamic banking. This study applies a qualitative method using a descriptive approach. Data in this study were collected through observation, interviews, and documentation. The results of this study indicate that the community in Air Tiris District is aware of the existence of Islamic banks. However, residents in this village still have minimal knowledge about the products and services offered by Islamic banks, and the lack of education about Islamic banking makes the residents more familiar with conventional banks.